2023
DOI: 10.3324/haematol.2022.282328
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin inhibitor vamifeport ameliorates ineffective erythropoiesis in a mouse model of β-thalassemia with blood transfusions

Abstract: β-thalassemia is an inherited anemia characterized by ineffective erythropoiesis. Blood transfusions are required for survival in transfusion-dependent β-thalassemia and are also occasionally needed in patients with non-transfusion-dependent β-thalassemia. Patients with transfusion-dependent β-thalassemia often have elevated transferrin saturation (TSAT) and non-transferrin-bound iron (NTBI) levels, which can lead to organ iron overload, oxidative stress, and vascular damage. Vamifeport is an oral ferroportin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therapeutic hepcidin mimetics (e.g., rusfertide) and hepcidin agonists (e.g., TMPRSS6 inhibitor and mini−hepcidin PR73 and mHS17) aim to reverse iron deficiency by targeting hepcidin−ferroportin axis, increase iron influx, mobilize tissue iron, and consequently normalize hematological parameters ( Chua et al, 2015 ; Makis et al, 2021 ; Handa et al, 2023 ). Furthermore, oral ferroportin inhibitors (e.g., vamifeport and substituted benzoimidazole compounds) can relieve ineffective erythropoiesis and improve body iron parameters in iron overload−associated TDT mice, as well as treat patients suffering from neurodegenerative and cardiac diseases ( Kadam et al, 2021 ; Kalleda et al, 2023 ). Previous studies have revealed that polyphenols dose dependently inhibit RBC hemolysis induced by AAPH, possibly by membrane anti-lipid peroxidation and protein antioxidation; EGCG and ECG had higher antioxidant capacity, while EGC and EC showed more effective ROS-radical scavenging activity ( Zhang et al, 1997 ; Zou et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic hepcidin mimetics (e.g., rusfertide) and hepcidin agonists (e.g., TMPRSS6 inhibitor and mini−hepcidin PR73 and mHS17) aim to reverse iron deficiency by targeting hepcidin−ferroportin axis, increase iron influx, mobilize tissue iron, and consequently normalize hematological parameters ( Chua et al, 2015 ; Makis et al, 2021 ; Handa et al, 2023 ). Furthermore, oral ferroportin inhibitors (e.g., vamifeport and substituted benzoimidazole compounds) can relieve ineffective erythropoiesis and improve body iron parameters in iron overload−associated TDT mice, as well as treat patients suffering from neurodegenerative and cardiac diseases ( Kadam et al, 2021 ; Kalleda et al, 2023 ). Previous studies have revealed that polyphenols dose dependently inhibit RBC hemolysis induced by AAPH, possibly by membrane anti-lipid peroxidation and protein antioxidation; EGCG and ECG had higher antioxidant capacity, while EGC and EC showed more effective ROS-radical scavenging activity ( Zhang et al, 1997 ; Zou et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%